High-protection composite coating on surface of bonded NdFeB magnet and preparation method of high-protection composite coating

Through the use of ZnCOF/Al-EPB coating liquid, the anode protection effect of zinc and aluminum and the carbon framework structure, combined with the permeability of resin and the dual polymerization network structure, the corrosion problem of bonded NdFeB magnets in humid environments is solved. It achieves efficient corrosion protection and magnetic performance protection.

CN119307151AActive Publication Date: 2025-01-14HEFEI UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411425195.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-14
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

The bonded NdFeB magnet is prone to corrosion in humid environments. The prior art anticorrosion coating has high brittleness and high internal stress, which affects the uniformity and bonding force of the coating.

Method used

ZnCOF/Al-EPB coating solution is used to prepare zinc metal organic frame aluminum composite material through hydrothermal synthesis, and combine it with benzoxazine blended epoxy resin system to form a composite coating, using the anode protection effect of zinc and aluminum The carbon frame structure improves corrosion resistance, and the permeability of the resin fills the carbonized pore structure to form a dual polymer network structure to improve hydrophobicity and adhesion.

Benefits of technology

The corrosion degree of bonded NdFeB magnets is significantly reduced, the chemical corrosion resistance and magnetic stability of the coating are improved, and the high protection effect of the coating is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307151A_ABST
    Figure CN119307151A_ABST
Patent Text Reader

Abstract

The invention discloses a bonded NdFeB magnet surface high-protection composite coating and a preparation method thereof, and belongs to the technical field of magnet surface protection. The composite coating is formed by spraying a ZnCOF / Al-EPB coating solution; the preparation method comprises the following steps: pretreating the surface of the bonded NdFeB magnet as a substrate; and spraying the ZnCOF / Al-EPB coating liquid on the surface of a substrate by adopting an air spraying process, and curing at 200-250 DEG C to obtain the ZnCOF / Al-EPB composite coating. According to the composite coating, the corrosion degree of the bonded NdFeB magnet can be remarkably reduced, and the influence of the composite coating on the magnetic performance of the bonded NdFeB magnet is small.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of magnet surface protection, and in particular relates to a high-protection composite coating on the surface of a bonded NdFeB magnet and a preparation method thereof. Background Art

[0002] As a special composite material, bonded NdFeB magnets have the advantages of easy mass production and easy manufacturing of complex shapes. They also have the advantages of low density, stable magnetic properties, and multi-polarized magnetization. Bonded NdFeB material is a NdFeB bonded material obtained by uniformly mixing the processed NdFeB quenching powder with resin, plastic or other low-melting-point metal binders, and then pressing, extruding or injection molding. The magnetic phase that makes up the bonded NdFeB magnet is a relatively complete Nd2Fe 14 B grains have a structure closer to a single phase, with a complete grain structure and smooth grain boundaries, and are generally not easily corroded. However, their metastable Nd-rich grain boundaries and Laves phases are very susceptible to corrosion in a humid environment.

[0003] Patent document CN114582618A provides a doped nanoparticle composite coating and a preparation method thereof, which forms a nano-phosphating layer on the surface of a sintered NdFeB magnet, and then applies an organic resin layer on the phosphating layer by cathode electrophoresis, and obtains a composite anti-corrosion coating after curing. However, the organic resin is relatively brittle after curing, and generates large internal stress during the curing process, which may affect the uniformity and bonding strength of the coating. Therefore, there is an urgent need for a highly protective composite coating on the surface of a bonded NdFeB magnet and a preparation method thereof to solve the above problems. Summary of the invention

[0004] One of the purposes of the present invention is to provide a highly protective composite coating on the surface of a bonded NdFeB magnet to solve the problem that the existing bonded NdFeB magnet has poor corrosion resistance;

[0005] The second object of the present invention is to provide a method for preparing a high-protection composite coating on the surface of a bonded NdFeB magnet.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] In the first aspect, a high-protection composite coating on the surface of a bonded NdFeB magnet is sprayed with a ZnCOF / Al-EPB coating liquid;

[0008] The composite coating has a thickness of 25-35 μm.

[0009] Furthermore, the preparation method of the ZnCOF / Al-EPB coating liquid comprises the following steps:

[0010] S1. Add Zn(NO3)26H2O (zinc nitrate hexahydrate) and H3BTC (trimesic acid) to anhydrous ethanol, mix well, react at 90-110°C for 8-10h, cool naturally to room temperature (25-30°C), add Al powder, stir for 1-2h, and vacuum dry to obtain a zinc metal organic framework aluminum composite material, recorded as ZnMOF / Al;

[0011] S2. Place ZnMOF / Al in a N2 atmosphere, uniformly heat to 600-800°C and calcine for 3-4h to obtain a zinc metal organic framework aluminum carbon-based composite material, recorded as ZnCOF / Al;

[0012] S3. PBa (bisphenol A type benzoxazine) and siloxane-containing epoxy resin are added to dichloromethane, and ultrasonically mixed to obtain benzoxazine-blended epoxy resin, recorded as EPB, and then ZnCOF / Al is added and stirred for 3-6 hours to obtain ZnCOF / Al-EPB coating liquid.

[0013] Furthermore, the molar ratio of Zn(NO3)26H2O, H3BTC and Al powder in S1 is 1:0.4-0.6:0.5-0.7.

[0014] Furthermore, the uniform heating rate in S2 is 6-8°C / min.

[0015] Furthermore, the usage ratio of PBa, siloxane-containing epoxy resin and dichloromethane in S3 is 0.4-0.6 g: 1 g: 12-14 mL.

[0016] Furthermore, the amount of ZnCOF / Al in S3 is 70-80% of the total amount of PBa and the siloxane-containing epoxy resin.

[0017] In a second aspect, a method for preparing a high-protection composite coating on the surface of a bonded NdFeB magnet comprises the following steps:

[0018] Step 1, pre-treating the surface of the bonding NdFeB magnet as a substrate;

[0019] Step 2: Use air spraying process to spray the ZnCOF / Al-EPB coating liquid onto the surface of the substrate, and then cure it at 200-250° C. to obtain a composite coating, which is recorded as ZnCOF / Al-EPB layer.

[0020] Furthermore, the pretreatment method in step 1 is specifically to perform chamfering and polishing, ultrasonic water washing, drying at 45-65° C., and naturally cooling to room temperature on the bonded NdFeB magnet.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. The high-protection composite coating on the surface of the bonded NdFeB magnet provided by the present invention is sprayed by ZnCOF / Al-EPB coating liquid. The composite coating can significantly reduce the corrosion degree of the bonded NdFeB magnet and has little effect on the magnetic properties of the bonded NdFeB magnet.

[0023] 2. The present invention adopts the composite method of ZnCOF / Al and EPB resin system. Since the zinc metal organic framework aluminum carbon-based composite material has a special pore structure, the good permeability of EPB resin further fills the carbonized pore structure, making the possible corrosion path of the ZnCOF / Al-EPB layer more tortuous. ZnCOF / Al acts as an anode to protect the cathode. The corrosive medium first reacts with Zn and Al to produce an oxide film. The oxide film will continue to be consumed and regenerated during the contact with the corrosive medium, slowing down the corrosion process; in addition, the carbon skeleton structure and EPB resin improve the surface hydrophobicity of the coating, better shield moisture, and effectively improve the chemical corrosion resistance of the coating.

[0024] 3. The zinc metal organic framework with a spherical structure is prepared by hydrothermal synthesis. It has a large number of void structures and a large specific surface area. The ZnMOF / Al formed by compounding with Al powder is sintered to obtain a carbonized skeleton structure. Zn and Al elements are evenly distributed on the carbonized skeleton structure, which can withstand high temperature and corrosion by acid and alkali solutions. ZnCOF / Al has good chemical stability. Since Zn and Al belong to negative potential in the electrochemical system, electron loss is prone to occur. In a corrosive environment, ZnCOF / Al with a carbon skeleton structure is oxidized as an anode sacrifice, and further chemical reactions occur to form a protective film to protect the substrate. During the corrosion process, ZnCOF / Al can not only prevent the corrosive medium from invading the substrate, but also react with the corrosive medium, so it is consumed in large quantities, which slows down the corrosion process to a certain extent.

[0025] 4. Bisphenol A benzoxazine is introduced into the siloxane-containing epoxy resin system, and the oxazine ring in the bisphenol A benzoxazine structure undergoes a ring-opening reaction to generate hydroxyl groups, which are used as catalysts and curing initiators for the siloxane-containing epoxy resin to further catalyze the ring-opening of the siloxane-containing epoxy resin, thereby realizing the formation of a Si-O-Si cross-linked network structure and improving the hydrophobicity of the coating surface. The dual polymer network structure and ZnCOF / Al synergistically improve the density of the coating, thereby significantly improving the hydrophobicity of the coating and preventing the penetration of corrosive media such as H and O. On the other hand, during the blending process of the siloxane structure in the siloxane-containing epoxy resin and bisphenol A-type benzoxazine, it may react with water to hydrolyze to form silanol (-Si-OH), which further reacts with the hydroxyl group on the surface of the substrate to form a Si-O-Fe covalent bond at the interface between the coating and the substrate, so that the substrate and the coating have a strong adhesion; in addition, the excess silanol generated by the siloxane structure during the system reaction can undergo a condensation reaction to form a Si-O-Si cross-linked network, so that the composite coating and the substrate are more closely attached. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The present invention will be further described below in conjunction with the accompanying drawings.

[0027] Figure 1 It is a schematic diagram of the preparation process flow of the ZnCOF / Al-EPB coating liquid in the present invention. DETAILED DESCRIPTION

[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] See also Figure 1 , a method for preparing a ZnCOF / Al-EPB coating liquid, comprising the following steps:

[0030] S1. Add Zn(NO3)26H2O and H3BTC to anhydrous ethanol, mix well, react at 90-110℃ for 8-10h, cool naturally to room temperature, add Al powder, stir for 1-2h, and vacuum dry to obtain a zinc metal organic framework aluminum composite material, recorded as ZnMOF / Al; the molar ratio of Zn(NO3)26H2O, H3BTC and Al powder is 1:0.4-0.6:0.5-0.7;

[0031] S2. placing ZnMOF / Al in a N2 atmosphere, uniformly heating to 600-800°C at a rate of 6-8°C / min, and calcining for 3-4h to obtain a zinc metal organic framework aluminum carbon-based composite material, recorded as ZnCOF / Al;

[0032] S3. PBa and the silicone-containing epoxy resin are added to dichloromethane, and ultrasonically mixed to obtain a benzoxazine-blended epoxy resin, recorded as EPB, and then ZnCOF / Al in an amount of 70-80% of the total amount of PBa and the silicone-containing epoxy resin is added, and stirred for 3-6 hours to obtain a ZnCOF / Al-EPB coating liquid; the amount ratio of PBa, silicone-containing epoxy resin and dichloromethane is 0.4-0.6g:1g:12-14mL.

[0033] A method for preparing a high-protection composite coating on the surface of a bonded NdFeB magnet comprises the following steps:

[0034] Step 1, chamfering and polishing the bonded NdFeB magnet with a double-end grinder and a rotary roller grinder, with an R angle of 0.2, washing with water in an ultrasonic cleaner for two stages, drying at 45-65°C, and naturally cooling to room temperature to obtain a substrate;

[0035] Step 2: Use air spraying process to spray ZnCOF / Al-EPB coating liquid on the surface of the substrate, and then cure it at 200-250° C. to obtain a composite coating, recorded as ZnCOF / Al-EPB layer, with a thickness of 25-35 μm.

[0036] Example 1

[0037] See also Figure 1 , a method for preparing a ZnCOF / Al-EPB coating solution, comprising the following steps:

[0038] S1. 1 mol Zn(NO3)26H2O and 0.5 mol H3BTC were added to anhydrous ethanol, mixed evenly, reacted at 100°C for 9 h, cooled naturally to room temperature, and then 0.6 mol Al powder was added. After stirring at 200 rpm for 1.5 h, the mixture was dried in vacuum to obtain a zinc metal organic framework aluminum composite material, which was recorded as ZnMOF / Al.

[0039] S2. Place ZnMOF / Al in a N2 atmosphere, uniformly heat to 700°C at a rate of 7°C / min and calcine for 3.5h to obtain a zinc metal organic framework aluminum carbon-based composite material, denoted as ZnCOF / Al;

[0040] S3. PBa and KH560 were added to dichloromethane, and ultrasonically mixed to obtain benzoxazine-blended epoxy resin, recorded as EPB, and then ZnCOF / Al in an amount of 75% of the total amount of PBa and KH560 was added, and stirred at 150 rpm for 4 hours to obtain ZnCOF / Al-EPB coating liquid; the amount ratio of PBa, KH560 and dichloromethane was 0.5g:1g:14mL.

[0041] Example 2

[0042] See also Figure 1 , a method for preparing a ZnCOF / Al-EPB coating solution, comprising the following steps:

[0043] S1. 1 mol Zn(NO3)26H2O and 0.4 mol H3BTC were added to anhydrous ethanol, mixed evenly, reacted at 100°C for 9 h, cooled naturally to room temperature, and then 0.5 mol Al powder was added. After stirring at 200 rpm for 1.5 h, the zinc metal organic framework aluminum composite material was obtained by vacuum drying, which was recorded as ZnMOF / Al.

[0044] S2. Place ZnMOF / Al in a N2 atmosphere, uniformly heat to 700°C at a rate of 7°C / min and calcine for 3.5h to obtain a zinc metal organic framework aluminum carbon-based composite material, denoted as ZnCOF / Al;

[0045] S3. PBa and KH560 were added to dichloromethane, and ultrasonically mixed to obtain benzoxazine-blended epoxy resin, recorded as EPB, and then ZnCOF / Al in an amount of 70% of the total amount of PBa and KH560 was added, and stirred at 150 rpm for 4 hours to obtain ZnCOF / Al-EPB coating liquid; the amount ratio of PBa, KH560 and dichloromethane was 0.4g:1g:14mL.

[0046] Example 3

[0047] See also Figure 1 , a method for preparing a ZnCOF / Al-EPB coating solution, comprising the following steps:

[0048] S1. 1 mol Zn(NO3)26H2O and 0.6 mol H3BTC were added to anhydrous ethanol, mixed evenly, reacted at 100°C for 9 h, cooled naturally to room temperature, and then 0.7 mol Al powder was added. After stirring at 200 rpm for 1.5 h, the mixture was dried in vacuum to obtain a zinc metal organic framework aluminum composite material, which was recorded as ZnMOF / Al.

[0049] S2. The ZnMOF / Al was placed in a N2 atmosphere, and the temperature was uniformly raised to 700°C at a rate of 7°C / min and calcined for 3.5h to obtain a zinc metal organic framework aluminum carbon-based composite material, which was recorded as ZnCOF / Al;

[0050] S3. PBa and KH560 were added to dichloromethane, and ultrasonically mixed to obtain benzoxazine-blended epoxy resin, recorded as EPB, and then ZnCOF / Al in an amount of 80% of the total amount of PBa and KH560 was added, and stirred at 150 rpm for 4 hours to obtain ZnCOF / Al-EPB coating liquid; the amount ratio of PBa, KH560 and dichloromethane was 0.6 g: 1 g: 14 mL.

[0051] Example 4

[0052] A method for preparing a high-protection composite coating on the surface of a bonded NdFeB magnet comprises the following steps:

[0053] Step 1, chamfering and polishing the bonded NdFeB magnet by a double-end grinder and a rotary roller grinder, with an R angle of 0.2, washing it with water in an ultrasonic cleaner for two stages, drying it at 50°C, and cooling it naturally to room temperature to obtain a substrate;

[0054] Step 2: The ZnCOF / Al-EPB coating liquid prepared in Example 1 was sprayed onto the substrate surface by air spraying, and then cured at 220° C. The resulting composite coating was referred to as the ZnCOF / Al-EPB layer and had a thickness of 30 μm.

[0055] Example 5

[0056] A method for preparing a high-protection composite coating on the surface of a bonded NdFeB magnet, which differs from Example 4 in that in step 2, the ZnCOF / Al-EPB coating liquid prepared in Example 2 is used for substrate spraying, and the remaining steps and parameters remain the same.

[0057] Example 6

[0058] A method for preparing a high-protection composite coating on the surface of a bonded NdFeB magnet is different from Example 4 in that in step 2, the ZnCOF / Al-EPB coating liquid prepared in Example 3 is used for substrate spraying, and the remaining steps and parameters remain the same.

[0059] Comparative Example 1

[0060] A method for preparing a ZnCOF / Al-EP coating liquid comprises the following steps:

[0061] S1 and S2 are the same as in Example 1;

[0062] S3. Add KH560 to dichloromethane, mix evenly by ultrasonication, then add ZnCOF / Al in an amount of 75% of the total amount of KH560, stir at 150 rpm for 4 hours to obtain a ZnCOF / Al-EP coating liquid; the amount ratio of KH560 to dichloromethane is 1 g:14 mL.

[0063] Comparative Example 2

[0064] A method for preparing a ZnCOF / Al-EB coating solution comprises the following steps:

[0065] S1 and S2 are the same as in Example 1;

[0066] S3. PBa was added to dichloromethane, and ultrasonic mixing was performed. Then, ZnCOF / Al in an amount of 75% of the total amount of PBa was added, and the mixture was stirred at 150 rpm for 4 h to obtain a ZnCOF / Al-EB coating liquid. The ratio of PBa to dichloromethane was 1 g:14 mL.

[0067] Comparative Example 3

[0068] A method for preparing a Zn / Al-EPB coating liquid comprises the following steps:

[0069] PBa and KH560 were added to dichloromethane and ultrasonically mixed to obtain a benzoxazine-blended epoxy resin, recorded as EPB, and then Zn powder and Al powder (the molar ratio of Zn powder to Al powder was 1:0.6) in an amount of 75% of the total amount of PBa and KH560 were added, and stirred at 150 rpm for 4 hours to obtain a Zn / Al-EPB coating liquid; the amount ratio of PBa, KH560 and dichloromethane was 0.5 g:1 g:14 mL.

[0070] Comparative Example 4

[0071] A method for preparing a Zn / Al-EP coating liquid comprises the following steps:

[0072] KH560 was added to dichloromethane, and the mixture was uniformly mixed by ultrasonication. Then, Zn powder and Al powder (the molar ratio of Zn powder to Al powder was 1:0.6) in an amount of 75% of the total amount of KH560 were added, and the mixture was stirred at 150 rpm for 4 hours to obtain a Zn / Al-EP coating liquid. The dosage ratio of KH560 to dichloromethane was 1 g:14 mL.

[0073] Comparative Example 5

[0074] A method for preparing a bonded NdFeB magnet surface protective composite coating, which differs from Example 4 in that in step 2, the ZnCOF / Al-EP coating liquid prepared in Comparative Example 1 is used to spray the substrate, and the remaining steps and parameters remain the same.

[0075] Comparative Example 6

[0076] A method for preparing a protective composite coating on the surface of a bonded NdFeB magnet is different from Example 4 in that in step 2, the ZnCOF / Al-EB coating liquid prepared in Comparative Example 2 is used to spray the substrate, and the remaining steps and parameters remain the same.

[0077] Comparative Example 7

[0078] A method for preparing a bonded NdFeB magnet surface protective composite coating is different from Example 4 in that in step 2, the Zn / Al-EPB coating liquid prepared in Comparative Example 3 is used to spray the substrate, and the remaining steps and parameters remain the same.

[0079] Comparative Example 8

[0080] A method for preparing a protective composite coating on the surface of a bonded NdFeB magnet is different from Example 4 in that in step 2, the Zn / Al-EP coating liquid prepared in Comparative Example 4 is used to spray the substrate, and the remaining steps and parameters remain the same.

[0081] The performance test was conducted on the composite coating prepared by bonding the surface of NdFeB magnets in Examples 4 to 6 and Comparative Examples 5 to 8:

[0082] (I) Neutral Salt Spray Test (NSS): Conducted by continuous spray test. Test conditions: spray box temperature 35℃±2℃, test solvent 5%±1% NaCl solution (mass fraction), saturated pressure barrel temperature 48℃, atomizing compressed air 98kPa, salt spray deposition 1.0-2.0 / 80cm 2 h. The pH of the collected salt spray precipitation solution is between 6.5-7.2; the sample is suspended, and its placement angle has an impact on the test results. The tilt angle of the sample surface in the salt spray chamber is 20°±5. According to the test time, observe the corrosion state of the test sample at fixed intervals. When the first visible corrosion product appears on the test sample, the time ends, and the corresponding time is the neutral salt spray resistance time of the sample.

[0083] (II) Self-corrosion potential (E corr ) Test: The electrochemical experiment was carried out using a standard three-electrode system. The sample to be tested was used as the working electrode, the Pt electrode was used as the counter electrode, the saturated calomel electrode was used as the reference electrode, and the 3.5% NaCl solution was used as the corrosion medium. The initial voltage of the test was -1.4V, the end voltage was 0.2V, and the scan rate was 0.005V·s -1 According to the potential value and current density value, the potential corresponding to the intersection of the cathode curve and the anode curve in the potentiodynamic polarization curve is the self-corrosion potential.

[0084] (III) Static contact angle test: Tested using a water contact angle meter.

[0085] (IV) Coating adhesion test: Adopt ASTM D3359 Method B and GB-T9286-1998 and scanning electron microscope test, and determine the adhesion level according to GB adhesion standard.

[0086] (V) Magnetic flux loss (△Ф / %) test: The NIM-200C magnetic property tester was used to test the magnetic properties of bare bonded NdFeB magnets and surface treated magnets to compare the magnetic flux loss.

[0087] The test results are shown in Table 1.

[0088] Table 1

[0089]

[0090] It can be seen from the above test results that the present invention introduces a metal organic framework structure into the ZnAl coating and further composites it with a bisphenol A type benzoxazine-silicone-containing epoxy resin dual polymer network structure, utilizes the leveling property of the resin to improve the hydrophobicity of the coating, and at the same time penetrates and fills the carbonized pores, thereby effectively improving the corrosion resistance of the coating, and the composite layer has almost no effect on the magnetic properties of the bonded NdFeB magnet.

[0091] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0092] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A high protection composite coating on the surface of a bonded NdFeB magnet, characterized in that: Made by spraying ZnCOF / Al-EPB coating liquid; The composite coating has a thickness of 25-35 μm.

2. A high protection composite coating on the surface of a bonded NdFeB magnet according to claim 1, characterized in that: The preparation method of the ZnCOF / Al-EPB coating liquid comprises the following steps: S1. Add Zn(NO3)26H2O and H3BTC to anhydrous ethanol, mix well, react at 90-110°C for 8-10h, cool naturally to room temperature, add Al powder, stir for 1-2h, and vacuum dry to obtain ZnMOF / Al; S2. Place ZnMOF / Al in a N2 atmosphere, uniformly heat to 600-800°C and calcine for 3-4h to obtain ZnCOF / Al; S3. PBa and siloxane-containing epoxy resin are added to dichloromethane, and ultrasonically mixed to obtain EPB, and then ZnCOF / Al is added and stirred for 3-6 hours to obtain ZnCOF / Al-EPB coating liquid.

3. A high protection composite coating on the surface of a bonded NdFeB magnet according to claim 2, characterized in that: The molar ratio of Zn(NO3)26H2O, H3BTC and Al powder in S1 is 1:0.4-0.6:0.5-0.

7.

4. A high protection composite coating on the surface of a bonded NdFeB magnet according to claim 2, characterized in that: The uniform heating rate in S2 is 6-8°C / min.

5. A high protection composite coating on the surface of a bonded NdFeB magnet according to claim 2, characterized in that: The usage ratio of PBa, silicone-containing epoxy resin and dichloromethane in S3 is 0.4-0.6 g: 1 g: 12-14 mL.

6. A high protection composite coating on the surface of a bonded NdFeB magnet according to claim 2, characterized in that: The amount of ZnCOF / Al in S3 is 70-80% of the total amount of PBa and silicone-containing epoxy resin.

7. A method for preparing a high-protection composite coating on the surface of a bonded NdFeB magnet as claimed in claim 1, characterized in that: The following steps are involved: Step 1, pre-treating the surface of the bonding NdFeB magnet as a substrate; Step 2: Use air spraying process to spray the ZnCOF / Al-EPB coating liquid on the surface of the substrate, and then cure it at 200-250° C. to obtain a ZnCOF / Al-EPB composite coating.

8. The method for preparing a high-protection composite coating on the surface of a bonded NdFeB magnet according to claim 7, characterized in that: The pretreatment method in step 1 is specifically to perform chamfering and polishing, ultrasonic water washing, drying at 45-65° C., and naturally cooling to room temperature on the bonded NdFeB magnet.

Citation Information

Patent Citations

  • Nanoparticle-doped composite coating as well as preparation method and application thereof

    CN114582618A

  • Silicon-containing benzoxazine resin as well as preparation method and application thereof

    CN102134254A

  • Graphene oxide / metal organic frame composite film, preparation method and application thereof

    CN110270234A

  • MOFs material modified epoxy composite coating and preparation method thereof

    CN115160893A